Magnetismo d0 em óxidos de In2O3 e (Sn1-xCex)O2 - Costa, Maria Helena Carvalho da (2019)
We investigated the structural, optical and magnetic properties of two nanoparticles oxide systems: In2O3, prepared by the high energy mechanical milling process, and (Sn1-xCex)O2 produced by the Pechini method, using different synthesis temperatures and the cerium concentration. The structural and morphological properties of nanoparticles were characterized by X-ray diffraction (XRD) techniques, using the Rietveld refinement, field emission scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution (HRTEM). The chemical composition and valence of the ions were investigated using X-ray photoelectron spectroscopy (XPS). Optical properties were studied using UV-Vis and photoluminescence (PL) techniques. Finally, magnetization measurements were performed using the SQUID magnetometry technique. The XRD measurements and the HRTEM images show that the formation of the cubic phase in In2O3 and the tetragonal SnO2 in the NPs of (Sn1-xCex)O2 as the main phases. In addition, in the process of obtaining the samples, we identified that the 96-h milling in the indium oxide led to the formation of the hexagonal phase, H- In2O3. When synthesizing samples of (Sn1-xCex)O2 at a temperature of 750 °C, an orthorhombic phase, O-SnO2, previously only encountered under high pressure and temperature, was formed. The stabilization of these phases at room temperature was associated with the effect of strain and/or defects that led to the establishment of ferromagnetism in our samples, exhibiting anomalous behaviour depending on the coercivity with temperature. We associate this behaviour to the effect of particle size distribution on the magnetic properties of indium oxide and the surface effects on the NPs of (Sn1-xCex)O2. The ferromagnetic behaviour observed in the NPs was related to the singly ionized oxygen vacancies on the surface of the NPs and with the effect of the strain.